Ginseng glycoprotein and ginsenoside facilitate anti UV damage effects in diabetic rats - Hu, Shuang; Huo, Lulu; He, Jing; Jin, Ye; Deng, Yongzhi; Liu, Da (Frontiers in Pharmacology, 2022)
Diabetes mellitus combined with ultraviolet (UV) radiation damage not only brings great mental stress to patients, but also seriously impairs their quality of life. A UV-irradiated diabetic rat trauma skin model was established by us to investigate the effects and possible mechanisms of ginsenoside and glycoprotein on skin trauma repair in UV-irradiated diabetic rats. In the study, ginsenosides and ginseng glycoproteins were extracted from different parts of ginseng roots. It found that it’s easier to prepare saponins in ginseng bark and proteins in ginseng core in large quantities. Since glycoprotein-like metabolites are relatively novel ginseng extracts, specifically characterized its structures. It was verified that the ginseng glycoproteins are not toxic to HaCaT cells and can significantly increase the survival of HaCaT cells after UV damage at the in vitro cellular level. Experiments in vivo were conducted to evaluate the therapeutic effects of ginsenoside and ginseng glycoprotein in a rat model of diabetes mellitus combined with UV irradiation injury. Histopathological changes on rat skin after treatment with ginsenoside and ginseng glycoprotein were evaluated by hematoxylin and eosin (H&E) staining and aldehyde fuchsine staining. The expression levels of malondialdehyde (MDA), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), matrix metalloproteinases (MMPs), hydroxyproline (HYP), interleukin-6 (IL-6), interleukin-1β (IL-1β), and tumor necrosis factor-α (TNF-α) were measured. The results indicate that both ginsenoside and ginseng glycoprotein could improve skin damage and ulcers caused by diabetes combined with UV irradiation and could alleviate a range of skin damage caused by the combination of diabetes and UV irradiation, including peroxidation and collagen fiber loss. Ginsenoside and ginseng glycoproteins can be considered as natural product candidates for the development of new drugs to treat diabetes combined with UV irradiation-induced skin damage.